Anais Do XIV Encontro Nacional De Estudantes De Engenharia Ambiental 2016
DOI: 10.5151/engpro-eneeamb2016-awrd-003-5098
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Da Filtração Lenta Como Tratamento De Águas Com Baixa Turbidez E Presença De Algas E Cianobactérias: Aplicação À Água Do Lago Paranoá/Df

Abstract: Resumo: A crescente demanda por água tratada tem requerido a utilização de novos mananciais de água para o abastecimento humano, como em breve ocorrerá com o lago Paranoá. Entretanto para adequada definição da tecnologia de tratamento a ser adotada faz-se necessário o conhecimento das características limnológicas e do ecossistema aquático. A filtração lenta é uma alternativa tecnológica que tem se mostrado eficiente na remoção partículas sólidas, cianobactérias e vários patógenos. Neste contexto, o objetivo do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…This means that upflow and downflow filters presented a similar ability to remove turbidity. Similar behavior is reported by Teixeira et al [19]. The authors operated two identical pilot filters, one upflow and the other downflow, under different filtration rates, to treat water with low turbidity.…”
Section: Turbidity and Head Loss Developmentsupporting
confidence: 77%
See 1 more Smart Citation
“…This means that upflow and downflow filters presented a similar ability to remove turbidity. Similar behavior is reported by Teixeira et al [19]. The authors operated two identical pilot filters, one upflow and the other downflow, under different filtration rates, to treat water with low turbidity.…”
Section: Turbidity and Head Loss Developmentsupporting
confidence: 77%
“…In the literature, there are examples of works that investigated the removal of Cryptosporidium oocysts and/or their surrogates through a direct filtration process, either using a downflow filter or an upflow filter [5,6,[8][9][10]12,13,[17][18][19]. However, no study was found comparing these two types of filters operating under similar conditions and assessing the removal efficiency of turbidity and oocyst surrogates.…”
Section: Introductionmentioning
confidence: 99%